Cardiopulmonary bypass associated acute kidney injury: better understanding and better prevention - Xutao Yang; Li Zhu; Hong Pan; Yi Yang (Renal Failure)
Cardiopulmonary bypass (CPB) is a common technique in cardiac surgery but is associated with acute kidney injury (AKI), which carries considerable morbidity and mortality. In this review, we explore the range and definition of CPB-associated AKI and discuss the possible impact of different disease recognition methods on research outcomes. Furthermore, we introduce the specialized equipment and procedural intricacies associated with CPB surgeries. Based on recent research, we discuss the potential pathogenesis of AKI that may result from CPB, including compromised perfusion and oxygenation, inflammatory activation, oxidative stress, coagulopathy, hemolysis, and endothelial damage. Finally, we explore current interventions aimed at preventing and attenuating renal impairment related to CPB, and presenting these measures from three perspectives: (1) avoiding CPB to eliminate the fundamental impact on renal function; (2) optimizing CPB by adjusting equipment parameters, optimizing surgical procedures, or using improved materials to mitigate kidney damage; (3) employing pharmacological or interventional measures targeting pathogenic factors.